2020
DOI: 10.1111/ane.13296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and safety profile of Tenecteplase in wake‐up stroke

Abstract: Background: Tenecteplase has probably pharmacological and clinical advantages in the treatment of acute ischemic stroke. There are lacking data about safety and efficacy of tenecteplase in wake-up stroke (WUPS). Aims: To investigate safety and efficacy of tenecteplase compared to alteplase in WUPS patients included in NOR-TEST. Methods: WUPS patients in NOR-TEST were included in the study based on DWI-FLAIR mismatch. Included patients randomly assigned (1:1) to receive intravenous tenecteplase 0.4 mg/kg (to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…A study by Ahmed et al (2020) that compared tenecteplase to alteplase for wake-up stroke thrombolysis showed no significant difference in the favorable outcomes after three months and safety In terms of safety and effectiveness, the results obtained in this study were consistent with other reports on this topic. However, in most cases, the current diagnostic and treatment guidelines were followed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study by Ahmed et al (2020) that compared tenecteplase to alteplase for wake-up stroke thrombolysis showed no significant difference in the favorable outcomes after three months and safety In terms of safety and effectiveness, the results obtained in this study were consistent with other reports on this topic. However, in most cases, the current diagnostic and treatment guidelines were followed.…”
Section: Discussionsupporting
confidence: 89%
“…However, despite the updated guidelines and increasingly common diagnostic options in neuroimaging, including perfusion and diffusion neuroimaging (Fink et al, 2002), there are still little data on the safety and efficacy of intravenous alteplase or mechanical thrombectomy in wake-up stroke. Ahmed et al (2020) demonstrated that most patients (65.2%) who were treated using a wake-up protocol that included alteplase and that was based on DWI/FLAIR mismatch exhibited a favorable functional outcomes 90 days after thrombolysis (mRs score = 0-1). A study by Aoki et al (2011) that was based on DWI/FLAIR mismatch found no incidence of symptomatic hemorrhage and a moderate rate (40%) of asymptomatic hemorrhage among patients with wake-up strokes who were treated with alteplase.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis 35 of the NOR-TEST trial 16 showed that among patients with DWI-fluid attenuated inversion recovery (FLAIR) mismatch, those in the 0.4 mg/kg TNK group had greater early neurological improvement than patients in the alteplase group (NIHSS reduction≥4: 87.5% vs 54.2%, P=0.027). However, selection bias cannot be neglected for the small sample size and low baseline NIHSS score in this subgroup study.…”
Section: Ct Perfusion (Ctp)/mr Mismatch Groupmentioning
confidence: 99%
“…23 However, numerous investigations have demonstrated no substantial difference in clinical severity or outcomes between WUS and stroke with known onset time, implying the feasibility of reperfusion therapy for patients who had a WUS. [24][25][26] Considering afore-mentioned literatures, there is still some debate about whether or not to treat patients who had a WUS with recanalisation therapy. As a result, further research is needed to validate the feasibility of recanalisation therapy for patients with WUS.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Patients with WUS had a greater likelihood of experiencing adverse outcomes and had a substantial effect on the modified Rankin Scale (mRS) Score increasing functional dependence 23. However, numerous investigations have demonstrated no substantial difference in clinical severity or outcomes between WUS and stroke with known onset time, implying the feasibility of reperfusion therapy for patients who had a WUS 24–26. Considering afore-mentioned literatures, there is still some debate about whether or not to treat patients who had a WUS with recanalisation therapy.…”
Section: Introductionmentioning
confidence: 99%